Comment on “Aesthetic conceptions and cultural symbols in traditional Chinese painting” - Jianxia Zhao (Trans/Form/Ação)
Commented Article: GUAN, Yan. Aesthetic conceptions and cultural symbols in traditional Chinese painting. Trans/Form/Ação: Unesp journal of philosophy, Marília, v. 47, n. 4, “Eastern thought”, e0240066, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14704.